Victims of Violence in Accident & Emergency: Reporting Survey of Eleven Emergency Structures Out of Eighteen - Maria Pia Ruggieri; Anna Santa Guzzo; Massimo Magnanti; Giannantonio Cerqua (Emergency Care Journal, 2011)
Sexual violence is a widespread and common phenomenon in our society, which unfortunately often goes unreported or undetected: a hidden “iceberg” of great dimension. Often the victims arrive to our emergency department where the sanitary workers are not prepared to help them professionally. By this work the authors want to evaluate health workers true understanding of the “problem of violence”; their human and professional capacity to manage it; their capacity to create and promote sensitisation and training programmes for professionals working in the field; and the ability to design and implement protocols and procedures to be utilized when managing victims of violence by a questionnaire compiled and distributed to health professionals working in the critical areas (A&E and DEA) in the region Lazio.